DEVDase detection in intact apoptotic cells using the cell permeant fluorogenic substrate, (z-DEVD)2-cresyl violet. (November 2003) - Lee, Brian W.; Johnson, Gary L.; Hed, Sally A.; Darzynkiewicz, Zbigniew; Talhouk, Jamil W.; Mehrotra, Sanjiv
Using a bisubstituted caspase-3 target sequence: aspartate-glutamate-valine-aspartate, (z-DEVD)2 peptide derivative of the fluorophore, cresyl violet, we have obtained a cell permeant, fluorogenic, caspase substrate capable of detecting the site-specific presence of functionally active, caspase-3 and caspase-7 up-regulation within intact apoptotic cells. Addition of this substrate to induced and noninduced cell culture populations allows for the rapid site-specific detection of caspase up-regulation without the requirement for a wash step. We demonstrate here the use of (z-DEVD)2 -cresyl violet substrate for the detection of apoptosis induction in Jurkat, THP-1, and MCF-7 cells using fluorescence microscopy and 96-well fluorescence plate reader analysis. Intracellular up-regulated DEVDase activity, which was clearly visible by fluorescence microscopy and 96-well fluorescence plate reader measurements, showed greater than 6-fold increases in fluorescence output in induced versus noninduced Jurkat cell samples. A simple fluorogenic substrate conversion method is demonstrated here for detecting apoptosis induction within intact living cells.